Feather Mathematics — Operator-Theoretic Proof of the Riemann Hypothesis (v1.0, Complete Proof Packet) - Sterling Dudley Hayden Independent Researcher — Feather Way Mathematics ORCID: https://orcid.org/0000-0002-XXXX-XXXX (AfricArXiv / UbuntuNet Alliance for Research & Education Networking, 2025)
Complete operator-theoretic proof packet for the Riemann Hypothesis (Feather Mathematics). This version consolidates the global proof (v0.9a), Fredholm continuity proofs (Appendix E), Archimedean constants (Appendix B), and final lemmas & constant fix (v1.0). It presents a unified operator–Fredholm formulation of the Riemann Hypothesis within the Feather Mathematics framework, grounded in Kemetic Ma’at principles of balance, order, and harmony. Riemann Hypothesis, Operator Theory, Fredholm Determinant, Ma’at, Kemetic Mathematics, African Mathematics, Feather Mathematics
Feather Mathematics v1.0 — Complete Proof of the Riemann Hypothesis
Complete operator-theoretic proof packet for the Riemann Hypothesis (Feather Mathematics). This version consolidates the global proof (v0.9a), Fredholm continuity proofs (Appendix E), Archimedean constants (Appendix B), and final lemmas & constant fix (v1.0). It provides a unified operator–Fredholm formulation of the Riemann Hypothesis within the Feather Mathematics framework, integrating Kemetic Ma’at principles of balance, order, and harmony into a rigorous modern operator-theoretic context.